GOVERNMENT VERSUS COMMUNITIES: PROVISION OF LOW-INCOME COMMUNITY HOUSING IN DAERAH ISTIMEWA YOGYAKARTA - Kurnia Fitri, Dionika Hayu; Swasto, Deva Fosterharoldas (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
Post-pandemic recovery in various sectors makes state and regional budget allocations unreliable for developing the housing sector. Even though the public's needs for housing continue to increase, coupled with the issue of limited land availability. To overcome that, the government began working to develop alternative financing for the housing sector through non-government funding, with the main target being the low-income community. Non-government funding is a non-conventional financing mechanism for infrastructure procurement through stakeholder collaboration. Daerah Istimewa Yogyakarta faces several issues regarding housing provisions for low-income communities. This research explores the prospects of implementing non-government schemes for low-income housing development through a comparative analysis between the community's willingness and ability and the policy stakeholder's capacity, potential trends, and future policy direction. The approach used in this research is deductive mixed methods, employing data collection through questionnaires to assess the willingness and ability of the community, as well as the Delphi method through expert interviews. This study reveals several disparities between the community's willingness and ability and the government's capacity as a provider. On the other hand, non- government funding for low-income housing is prospective in the long term, with specific considerations and preconditions. The result of this research is that by improving coordination between the community and the government, coupled with efforts to enhance mutual understanding and more effective communication between the two parties, holds the potential to advance the funding prospects for low-income housing development in Daerah Istimewa Yogyakarta. However, it requires a considerable amount of time under specific conditions.